Attitudes of Medical Malpractice in Pediatric Surgery - Ahmet Arıkan; Serkan Çınarlı; Fisun Şenuzun Aykar; Ali Sayan (Galenos Yayinevi, 2017)
Aim: The aim of this study was to evaluate the proportion of pediatric surgeons who committed medical malpractice (MM) while on duty in hospitals, whether this proportion changed according to age and experience, and if they reported MM or not, and to determine their level of knowledge related to the legal processes. Materials and Methods: A cross-sectional survey design was used with a two-part web-questionnaire developed by the authors. The web-questionnaire consisted of twenty-four questions and was prepared after a review of the relevant literature as required to address the aims of the study. Statistical analysis was conducted using SPSS 18.0. Results: One hundred and fifty-one pediatric surgeons answered the questionnaire; 46% were specialists, 87% were working in public hospitals, and 9% had never committed MM. The type of institution did not affect the occurrence of MM. The major factors that affected the occurrence of MM seemed to be lack of knowledge and experience alongside lack of attention. Working conditions and exhaustion played minor roles. While junior pediatric surgeons mostly committed MM in abdominal, urogenital, newborn and thoracic surgeries, the area was mostly newborn surgery for senior surgeons. Conclusion: Few MM cases were taken to court. Lack of experience, knowledge and attention play major roles in the occurrence of MM. MM cases should be archived meticulously.